2007
DOI: 10.1510/icvts.2007.165217
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic apico-posterior transmediastinal approach for bilateral spontaneous pneumothorax

Abstract: Thoracotomic, trans-sternal or thoracoscopic approaches through transmediastinal access for contralateral lung are operative alternatives for bilateral pulmonary lesions. Video-assisted thoracoscopic surgery (VATS) for spontaneous pneumothorax (PTX) is now considered as a standard approach. Herein, we report a novel method of apico-posterior transmediastinal ipsilateral approach using VATS to perform simultaneous bilateral bullectomy in two young men with simultaneous bilateral spontaneous PTX. This new VATS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Also this procedure has some contraindications, such as a history of sternotomy and intolerance to one-lung ventilation. We first reported a new VATS technique for BB via apicoposterior TM access to the contralateral side, 10 and then evaluated feasibility of this method in 10 selected BPSP patients. 11 Therefore, we compared the TM VATS with the BS VATS for simultaneously developed BPSP patients at our institution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also this procedure has some contraindications, such as a history of sternotomy and intolerance to one-lung ventilation. We first reported a new VATS technique for BB via apicoposterior TM access to the contralateral side, 10 and then evaluated feasibility of this method in 10 selected BPSP patients. 11 Therefore, we compared the TM VATS with the BS VATS for simultaneously developed BPSP patients at our institution.…”
Section: Discussionmentioning
confidence: 99%
“…The TM approach for BPSP was precisely described in two published papers. 10,11 Briefly, the patient was placed in leftdown decubitus position and right-side VATS approach was used under general anesthesia using one-lung ventilation with double-lumen endotracheal tube. Three thoracoports for a thoracoscope, an Endostapler, and other instruments were inserted at the fifth or sixth intercostal space (ICS) on the middle axillary line, and at the third or fourth ICS on the anterior and posterior axillary line.…”
Section: Operation Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Although a bilateral thoracoscopic approach is safe and well established according to several reports, it needs bilateral multiple incisional wounds, uses multiple surgical drapes, has a long surgical time, uses inconvenient bilateral CTDs, causes postoperative pain, and its recurrence rate is still controversial. A few reports demonstrate that transmediastinal contralateral approaches are a technically feasible and good therapeutic option in selected cases of BPTX [3, 6, 7]. Nazari et al [3] reported a new technique for BB and pleurectomy via subaxillary minithoracotomy and apicoposterior transmediastinal access to the contralateral side in 13 selected BPTX patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a few researchers [ 64 - 66 ] have introduced, as a further advanced novel procedure, a thoracoscopic ipsilateral transmediastinal approach to contralateral as well as ipsilateral bullous lesions in patients with bilateral pneumothorax in the supine position, although the results were obtained under limited situations. Further new techniques with the VATS procedure will likely be developed in the future.…”
Section: Surgical Approach To Both Lungsmentioning
confidence: 99%